Fabrication and characterization of drug-loaded nano-hydroxyapatite/polyamide 66 scaffolds modified with carbon nanotubes and silk fibroin - Yao MZ (Dove Medical Press, 2016)
Meng-Zhu Yao,1 Ming-Yi Huang-Fu,1 Hui-Na Liu,1 Xia-Rong Wang,1 Xiaoxia Sheng,2 Jian-Qing Gao1 1Institute of Pharmaceutics, College of Pharmaceutical Sciences, Zhejiang University, 2Hangzhou SoliPharma Co., Ltd, Hangzhou, Zhejiang, People’s Republic of China Abstract: Nano-hydroxyapatite/polyamide 66 (nHA/PA66) porous scaffolds were fabricated by a phase inversion method. Carbon nanotubes (CNTs) and silk fibroin (SF) were used to modify the surface of the nHA/PA66 scaffolds by freeze-drying and cross-linking. Dexamethasone was absorbed to the CNTs to promote the osteogenic differentiation of bone mesenchymal stem cells (BMSCs). The cell viability of BMSCs was investigated by changing the concentration of the CNT dispersion, and the most biocompatible scaffold was selected. In addition, the morphology and mechanical property of the scaffolds were investigated. The results showed that the nHA/PA66 scaffolds modified with CNTs and SF met the requirements of bone tissue engineering scaffolds. The dexamethasone-loaded CNT/SF-nHA/PA66 composite scaffold promoted the osteogenic differentiation of BMSCs, and the drug-loaded scaffolds are expected to function as effective bone tissue engineering scaffolds. Keywords: BMSCs, tissue engineering, porous scaffold, carbon nanotubes, silk fibroin, surface modification, dexamethasone